Al-Ghazali : Rekonsiliasi Syariat Dan Tasawuf - Supriadin, Irwan (At-Tuhfah : Jurnal Studi Keislaman, 2022)
This paper is a literature study using a qualitative descriptive approach that aims to describe al-Ghazali's ideas in reconciling Shari'a and Sufism. This study found that although al-Ghazali did not believe in Rasa (Dzawq), it did not cause him to doubt as a tool in reaching the truth. The basis for analyzing and understanding religious matters, while the concept of Ma'rifat which is the hallmark of al-Ghazali is a development of concepts that have existed before. In his efforts to reconcile Shari'ah and Sufism, al-Ghazali was able to explain the close relationship between Shari'ah and Sufism, but behind that, al-Ghazali was not yet fully able to place the two on the same level. This can be seen from the stratification – lay and concerned – for Muslims who do good deeds, so that they are unconsciously trapped in the tendency of Sufi superiority.